Infant Feeding and Childhood Obesity: A Critical Review - Phillips, Hannah (2011)
Childhood obesity is a global and national concern, costing the NHS approximately £4.2 billion every year, with serious health implications both in child and adulthood. A number of risk factors exist that may contribute to childhood obesity, modifiable and non-modifiable, and as suggested in this report, infant feeding may be a significant modifiable risk factor. In a discussion of selected reviews, breastfeeding has been shown to lead to lower weight gains and BMI‟s in both childhood and through to adolescence and those parents who turn to bottle feeding as an alternative may be increasing the risk of their infant becoming obese as this method of feeding may exert less self-control and regulation of feeding, resulting in overconsumption of calories and increased weight gains. Introducing solid foods into an infant‟s diet at an early age has also been shown in the discussed reviews to result in greater infant weight gains and obesity up to the age of ten years. Despite these links between infant feeding practices and childhood obesity, many studies have shown that no such link exists once confounding factors and study limitations have been controlled for. The early infancy environment may be a critical period for the development of obesity and thus health professionals may play a role in obesity prevention through the promotion and support of appropriate feeding practices during infancy. In order to avoid confusion amongst mothers with regards to correct infant feeding practices, it is essential that they are provided with correct and consistent advice from professionals. The role of the paediatric nurse in infant feeding education is therefore a critical one and any gaps in professional knowledge should be identified and addressed.